Zur Einbindung der Kapitaleinkommensbesteuerung in ein rationales Steuersystem - Stefan Homburg (Zeitschrift für Wirtschaftspolitik, 2005)
– Recent proposals for capital income tax reform are considered. The analysis focusses on German taxes, but experiences from abroad as well as the European Savings Directive are also taken into account. Given the present complexity of capital income taxation, the crucial question is whether or not Germany should adopt a dual income tax. After considering questions of distributive justice, tax yield, efficiency, and compliance, the article advocates in favour of a comprehensive income tax, combined with a strengthening of tax audit, and rejects the idea of a dual income tax.
Keywords: H24; 330; Capital income taxation; Kapitaleinkommensbesteuerung